2004
DOI: 10.1603/0022-2585-41.6.1055
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Responses of <I>Aedes aegypti</I> (Diptera: Culicidae) Exposed to Deltamethrin and Possible Implications for Disease Control

Abstract: Behavioral responses of nine Aedes aegypti (L.) strains, six from recent field collections and three from the long-established laboratory colonies, were tested under laboratory-controlled conditions by using an excito-repellency test system. All nine strains showed significant behavioral escape responses when exposed to deltamethrin at the standard field dose (0.02 g/m2), regardless of background insecticide susceptibility status (susceptible or tolerant/resistant). Insecticide contact irritancy played a predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 11 publications
4
50
0
1
Order By: Relevance
“…Although chlorpyrifos is considered a nonselective product , this acaricide did not affect the evaluated behavioural parameters of N. baraki, thereby suggesting that there may not be a relationship between the behavioural effects and toxicity for chlorpyrifos. Several authors have reported this same result for deltamethrin, permethrin, abamectin and fipronil (Kongmee et al 2004;Wang et al 2004;Jallow and Hoy 2005). The fact that carbosulfan changed the behavioural parameters confirmed the low tolerance of the mite to this product, as it was necessary to use the LC 50 values in the bioassays because the LC 99 concentrations paralysed the predator before the end of the experiment.…”
Section: Discussionmentioning
confidence: 61%
“…Although chlorpyrifos is considered a nonselective product , this acaricide did not affect the evaluated behavioural parameters of N. baraki, thereby suggesting that there may not be a relationship between the behavioural effects and toxicity for chlorpyrifos. Several authors have reported this same result for deltamethrin, permethrin, abamectin and fipronil (Kongmee et al 2004;Wang et al 2004;Jallow and Hoy 2005). The fact that carbosulfan changed the behavioural parameters confirmed the low tolerance of the mite to this product, as it was necessary to use the LC 50 values in the bioassays because the LC 99 concentrations paralysed the predator before the end of the experiment.…”
Section: Discussionmentioning
confidence: 61%
“…previous findings reported by Chareonviriyaphap et al (2004), Kongmee et al (2004), and Dusfour et al (2009). In these papers, pyrethroids had an irritant effect when mosquitoes came into contact with the treated surface.…”
Section: Discussionmentioning
confidence: 58%
“…The Ministry of Public Health of Thailand has used these two pyrethroid insecticides for space spraying applied via fogging or misting machines and mosquito net treatments (Chareonviriyaphap et al 1999, Jirakanjanakit et al 2007. Previous studies have found that both deltamethrin and permethrin elicit strong contact irritant response in mosquito vectors , 2012, Kongmee et al 2004, Mongkalangoon et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…In nature, A. gambiae is as likely to enter pyrethroid-containing as pyrethroid-absent huts but is much more likely to leave the former (see Takken, 2002). The mechanism underlying this behavior is often referred to as excito-repellent ( Mathenge et al, 2001;Kongmee et al, 2004)) though a recent paper by Cooperband and Allan (2009) suggests that pyrethroids are best described as locomotory stimulants because the exact mechanism underlying this response is not fully understood. In this case, the energetic cost of inter-hut flight and resetting of the information state must be considered.…”
Section: ) Seek a Blood Mealmentioning
confidence: 99%